SEKATEN MERUPAKAN UPACARA ADAT YANG BERNUANSA RELIGIUS - Ardinarto, E.S. (MIIPS, 2008)
E.S. Ardinarto, Sekaten is a Custom Ceremony Having Nuance of Religious.This research aim to: 1) Know the meaning os Sekaten Ceremony, 2) Nuance exists in Sekaten, 3) Since when Sekaten Ceremony started, 4) execution procedures of Sekaten Ceremony, 5) to know whether Sekaten Ceremony is a way of spreading Religion of Islam. Method used in this research is a qualitative anthropologic method that is descriptive analytic or constructing culture view. Strategy used in this research has been specified first before going into research location. Research location in Keraton Surakarta dan its surrounding, since those still conducting Sekaten Ceremony is those who live in Keraton Surakarta and Keraton Yogayakarta only. Data source obtained from informants that are keratonâs consanguinity who know exactly about Sekaten Ceremony, while techniques of gathering data are interview and direct observation but passive. Conclusions obtained are: 1) Sekaten Ceremony is a ceremony conducted only in keratin/ king, 2) Sekaten Ceremony is a combination ceremony between culture and religion, 3) Sekaten aims to express thanks of the king to the God who gave safety to keratin, 4) Sekaten Ceremony as a cultural heritage of ancestors having religious nuance.Â